Bread book : ideas and innovations from the future of grain, flour, and fermentation - Robertson, Chad; Latham, Jennifer (Lorena Jones Books, an imprint of Ten Speed Press, 2021)
The cofounder of Tartine bakery and bistro shares his knowledge of the craft and science of bread making with sixteen formulas for naturally leavened doughs--including baguettes, flatbread, rolls, tortillas, gluten-free loaves, and fermented pasta doughs that use discarded sourdough starter.